Associations between oral health impacts attributed to malocclusion and normative and self-perceived orthodontic treatment need in Turkish adolescent patients - Asuman Deniz Gümrü Çelikel; Muhsin Çifter; Beyza Tağrikulu; Kadriye Peker (BMC, 2024)
Abstract Background In the socio-dental approach, the integration of normative oral health-related quality of life (OHRQoL) and behavioral propensity measures should be considered when assessing treatment needs and planning oral services. Therefore, this study aimed to evaluate the relationship between oral health impacts attributed to malocclusion and normative and self-perceived orthodontic treatment needs in adolescent patients and to determine the clinical, sociodemographic, and behavioral factors affecting their OHRQoL. Methods This cross-sectional study was conducted using a convenience sample size of 105 adolescent patients aged 11-14 years who were referred to the Orthodontics Clinic in the Faculty of Dentistry, Istanbul. Data were collected using clinical examinations and a self-reported questionnaire, including the condition-specific Child Oral Impact on Daily Performances (CS-COIDP) attributed to malocclusion and sociodemographic, clinical, and behavioral factors. The index of complexity, outcome, and need (ICON), gingival index, and Decayed, Missing, Filled Teeth index was used to assess oral health status. Descriptive statistics and bivariate and multivariate regression analyses were used for the data analyses. Results A total of 70 patients (66.7%) reported at least one impact. Furthermore, 47% of the adolescents had very difficult and difficult complexity grades. The most affected performances were "emotional (52.4%) and smiling (40%)". No significant differences were found in the total CS-COIDP scores according to caries experience; however, the gingival status was associated with the total OHRQoL. Lower tooth brushing frequency, increased malocclusion complexity, and subjective treatment need were the most important predictors of worse OHRQoL, accounting for 39.3% of the variance in the scores. ( R2 = 0.422; p < 0.001) Conclusions Oral health professionals should consider oral behaviors, malocclusion complexity, and subjective treatment need when planning orthodontic treatment plans. Integrating ICON, CS-COIDP, and behavioral assessment will help identify adolescents who should be prioritized for treatment.